La coordinación de los deudores latinoamericanos : el Consenso de Cartagena y el Grupo de los Ocho - O'Connell, Arturo (Estudios Internacionales, 1988)
In May 1984, four Latin American presidents issued a joint statement on the international economic circumstances that seriously affected the continent, among them the rise in interest rates and protectionist measures. The declaration called for a meeting between the Foreign Ministers and the Ministers of the financial area of Latin American countries to define "initiatives and the most appropriate courses of action." This was the meeting that led to the creation of the Cartagena Consensus as a way of "maintaining a regional consultation and monitoring mechanism." In order to examine the coordination activity of debtors, in the Consensus and in the Group of Eight, the present work will distinguish between the elaboration of positions on the merits of the issue of external indebtedness and the initiatives regarding how to achieve success of the agreed objectives. As we will see, there is a strong link between these two areas.